2015
DOI: 10.1186/s12985-015-0430-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of the common avian leukosis virus subgroups by real-time loop-mediated isothermal amplification

Abstract: BackgroundSubgroups A, B, E and J are the major subgroups of avian leukosis virus (ALV) infecting chickens. ALV infection has become endemic in China and has a significant negative effect on the poultry industry. Consequently, there is an urgent need for a specific, sensitive and rapid method for diagnosis and eradication of ALV. Therefore, we developed a simple and rapid real-time loop-mediated isothermal amplification (LAMP) reaction for the timely detection of the common ALV subgroups, whereby the amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
(33 reference statements)
0
8
0
1
Order By: Relevance
“…Though the MD vaccines are capable of preventing lymphoma formation and clinical disease, do not prevent superinfection by pathogenic MDV strains [15]. Therefore, detection and elimination of infected birds form the basis for diagnosis and eradication programmes for oncogenic viruses [16]. In the present study, we investigated the samples from an outbreak, the lesions suspected of oncogenic viruses in poultry by histopathology of organs involved and molecular characterization of virus to understand the strain of virus present in the poultry flock in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Though the MD vaccines are capable of preventing lymphoma formation and clinical disease, do not prevent superinfection by pathogenic MDV strains [15]. Therefore, detection and elimination of infected birds form the basis for diagnosis and eradication programmes for oncogenic viruses [16]. In the present study, we investigated the samples from an outbreak, the lesions suspected of oncogenic viruses in poultry by histopathology of organs involved and molecular characterization of virus to understand the strain of virus present in the poultry flock in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Many LAMP assays have been developed and validated for important epizootic diseases, including 18 viruses thought notifiable of ruminants, swine and poultry by the World Organization for Animal Health (OIE) (Mansour et al, 2015). The LAMP assay was also developed for detection of the Tembusu virus (Tang et al, 2016), four immunosuppressive viruses (Song et al, 2018), avian leucosis virus (Peng et al, 2015), avian reovirus (Kumar et al, 2017), and found to be useful also in the detection of MDV in feathers and internal organs of infected chickens (Woźniakowski and Samorek-Salamonowicz, 2014). Direct detection of MDV DNA in poultry dust has been conducted without DNA extraction.…”
Section: The Loop-mediated Isothermal Amplificationmentioning
confidence: 99%
“…A group-specific primer for white spot syndrome virus should only amplify the 16 strains but no other viruses. Traditionally, the group-specific primers are designed based on conserved genes (Peng et al, 2015), genome regions (Yao et al, 2016) or the multiple sequence alignment (MSA) of these genes or genomic regions (Kurosaki et al, 2010). But this method is limited by the small number of suitable genes and the difficulty to generate MSA for a large number of sequences (Chen and Tompa, 2010).…”
Section: Introductionmentioning
confidence: 99%